2022
DOI: 10.7759/cureus.26194
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Fentanyl and Dexmedetomidine in Preventing an Increase in Heart Rate During Intubation Among Patients Undergoing General Anesthesia: A Meta-Analysis

Abstract: General anesthesia induction, tracheal intubation, extubation, and laryngoscopy are associated with specific hemodynamic changes. Tracheal intubation and laryngoscopy are related to sympathetic stimulation and lead to hypertension and tachycardia. Recent studies have shown that dexmedetomidine is safe and effective as it does not depress respiratory function. This meta-analysis aims to compare the efficacy of dexmedetomidine and fentanyl in preventing an increase in heart rate (HR) during intubation among pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Earlier studies have shown that dexmedetomidine provides a blunting response during laryngoscopy, intubation, skull pinning, and extubation in various surgeries under general anesthesia, which was similar to the result of this study [1,10,[12][13][14].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Earlier studies have shown that dexmedetomidine provides a blunting response during laryngoscopy, intubation, skull pinning, and extubation in various surgeries under general anesthesia, which was similar to the result of this study [1,10,[12][13][14].…”
Section: Discussionsupporting
confidence: 91%
“…Dexmedetomidine is an alpha-2 agonist, gaining popularity in neuroanesthesia as an adjuvant for its sympatholytic, sedative, and hemodynamic stabilizing properties without causing significant respiratory depression and a decrease in the need for anesthesia [7][8][9]. In one of the recent meta-analyses, dexmedetomidine was proven to be better at preventing tachycardia following endotracheal intubation than fentanyl [10].…”
Section: Introductionmentioning
confidence: 99%
“…Hence statistically significant bradycardia was not observed in our study compared to the other two groups. Mohsin et al [10] conducted a meta-analysis of clinical trials which compared the effectiveness of dexmedetomidine and fentanyl in avoiding elevation in HR during intubation and found that HR was significantly lower at 1 min, 5min and 10 mins post intubation in dexmedetomidine group. Das et al [11] compared fentanyl and dexmedetomidine in diminution of hemodynamic response to laryngoscopy and intubation and found that dexmedetomidine had significant fall in blood pressure than fentanyl (p-value=0.03) while there was no significant fall in heart rate between dexmedetomidine and fentanyl (p-value=0.…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine’s highly-selective agonistic action on presynaptic α2-adrenergic receptors and subsequent inhibition of norepinephrine release from the locus coeruleus has been hypothesized as the most putative mechanism for its hemodynamic stress response attenuating action [ 26 ]. Intravenous dexmedetomidine also attenuates the hemodynamic responses to laryngoscopy and ETI but is associated with risk of bradycardia, hypotension and cardiac arrests [ 4 , 9 , 10 , 14 , 27 , 28 ]. De Cassai et al in a recent SRMA of 99 RCTs involving 6833 patients found significant bradycardia in one out of every 12 patients [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine is a centrally acting α-2 adrenergic agonist with sedative, hypnotic, analgesic, anxiolytic, antisialagogue, antinociceptive and sympatholytic action [2,3]. Premedication with dexmedetomidine through intravenous, intramuscular and intranasal route has been shown to effectively attenuate hemodynamic response to laryngoscopy and ETI [4][5][6][7][8][9][10]. However, its use is associated with adverse effects like hypotension and bradycardia with intravenous route and nasal irritation with intranasal route [5][6][7][8]11].…”
Section: Introductionmentioning
confidence: 99%